Multivariate Analyses of Balance Test Performance, Vestibular Thresholds, and Age - Karmali, Faisal; Bermúdez Rey, María Carolina; Clark, Torin K.; Wang, Wei; Merfeld, Daniel M. (Frontiers in Neurology, 2017)
We previously published vestibular perceptual thresholds and performance in the Modified Romberg Test of Standing Balance in 105 healthy humans ranging from ages 18-80 (Bermúdez Rey et al., 2016). Self-motion thresholds in the dark included roll tilt about an earth-horizontal axis at 0.2 Hz and 1 Hz, yaw rotation about an earth-vertical axis at 1 Hz, y-translation (interaural/lateral) at 1 Hz and z-translation (vertical) at 1 Hz. In this paper, we focus on multiple variable analyses not reported in the earlier paper. Specifically, we investigate correlations 1) among the five thresholds measured and 2) between thresholds, age and the chance of failing condition 4 of the balance test, which increases vestibular reliance by having subjects stand on foam with eyes closed. We found moderate correlations (0.30-0.51) between vestibular thresholds for different motions, both before and after using our published aging regression to remove age effects. We found that lower or higher thresholds across all threshold measures are an individual trait that account for about 60% of the variation in the population. This can be further distributed into two components with about 20% of the variation explained by aging and 40% of variation explained by a single principal component that includes similar contributions from all threshold measures. When only roll tilt 0.2 Hz thresholds and age were analyzed together, we found that the chance of failing condition 4 depends significantly on both (p=0.006 and p=0.013, respectively). An analysis incorporating more variables found that the chance of failing condition 4 depended significantly only on roll tilt 0.2 Hz thresholds (p=0.046) and not age (p=0.10), sex nor any of the other four threshold measures, suggesting that some of the age effect might be captured by the fact that vestibular thresholds increase with age. For example, at 60 years of age, the chance of failing is roughly 5% for the lowest roll tilt thresholds in our population, but this increases to 80% for the highest roll tilt thresholds. These findings demonstrate the importance of roll tilt vestibular cues for balance, even in individuals reporting no vestibular symptoms and with no evidence of vestibular dysfunction.